2001
DOI: 10.1123/mcj.5.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Gait and Trunk Movements to Prehension: Perspectives from World- and Body-Centered Coordinates

Abstract: The present paper reviews a series of prehension experiments recently conducted at Simon Fraser University's Human Motor Systems Laboratory, and attempts to place them into the larger context of multi-segmental control theory. Two related lines of experiments are reported: (a) experiments involving prehension during walking, and (b) experiments involving trunk-assisted reaching. Three-dimensional analyses of movements were performed via both world-and body-centered coordinates. Our results are supportive of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…Trunk contribution to the reaching movement was examined using a methodology first reported by Marteniuk and colleagues (Marteniuk et al 2000;Marteniuk and Bertram 2001), which involved calculating the wrist coordinates from both world-centered and body-centered Significant differences between the two factors, condition and frame of reference, after post hoc analysis; where two conditions have the same superscript there was no significant difference for that variable frames of reference. This analysis revealed that children exhibited a different coordination between the trunk and arm in the three reach and grasp conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trunk contribution to the reaching movement was examined using a methodology first reported by Marteniuk and colleagues (Marteniuk et al 2000;Marteniuk and Bertram 2001), which involved calculating the wrist coordinates from both world-centered and body-centered Significant differences between the two factors, condition and frame of reference, after post hoc analysis; where two conditions have the same superscript there was no significant difference for that variable frames of reference. This analysis revealed that children exhibited a different coordination between the trunk and arm in the three reach and grasp conditions.…”
Section: Discussionmentioning
confidence: 99%
“…With adults participants, Marteniuk and colleagues (Marteniuk et al 2000;Marteniuk and Bertram 2001) demonstrated that the amount of trunk flexion and rotation varied according to whether they reached during standing or during locomotion. This finding required the use of a novel analysis procedure in which the movement of the hand was compared relative to a fixed, world-centered frame of reference (normally used in prehension research), and to a body-centered frame of reference (i.e., the trunk).…”
Section: Introductionmentioning
confidence: 99%
“…Although Georgopoulus and Grillner's paper is highly cited, only few subsequent studies have actually addressed the question of how walking and prehension are integrated and controlled. A common finding of these few studies is that reaching and grasping movements while walking are organized in hierarchical fashion, in a way that gait is adjusted based on the demands of the reaching and grasping task [2]. It has also been found that changes in gait imposed by the reaching task constraints may be task dependent [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…lifting), although a small number of studies have investigated the coordination between stepping and grasping (Cockell, Carnahan, and McFadyen 1995;Marteniuk and Bertram 2001;van der Wel and Rosenbaum 2007).…”
Section: Introductionmentioning
confidence: 99%